Development of Food Handling and Traceability System for Global Health Using Big Data and the Internet of Things (International Journal of Food and Nutritional Sciences, 2022)
In the way of managing and preventing epidemics, information analysis, food security accountability, and food quality and safety management have all grown in importance. At this point, incomplete, ambiguous, or asymmetrical insights are a major source of concern for food health and safety. The first step in addressing these concerns is to establish a secure and dependable food traceability system that is reasonably priced. The monitoring system is becoming an indispensable tool for ensuring availability and quality, as well as bridging the trust gap between consumers and the market. The unpredictability and complex data storage requirements of existing food security and hygiene traceability systems are addressed by studies on IoT, big data, and intelligent intelligence systems. This study proposes a food protection provenance system that makes utilization of the Web of Points' huge information storage capacity and RFID two-dimensional coding technology. It gives the example of rice. The present paper applies the concept of RFID to the entire system via an evaluation of needs, database table development, two-dimensional code registering, and style development. the use of big data and radio frequency identification (RFID) technologies to gather information about the food manufacturing process. Gradually, a mobile terminal and an interactive inquiry platform will make it feasible to keep an eye on every phase of food production. Using massive amounts of data and the Internet of Things, the proposed safety and security of food provenance system ensures the technical correctness, dependability, and security of traceability data. This is the best course of action to make sure that details are accurate, strengthen the foundation of the information retention system, and boost the legitimacy of traceability data.